STRATEGI KOLABORASI LEMBAGA ZAKAT DALAM MEWUJUDKAN PERCEPATAN PEMBANGUNAN EKONOMI UMAT DI KABUPATEN SIAK - Wiwik Indra Mariana (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2024)
Technological developments in Indonesia continue to improve, with many institutions now developing technology for their operations. These technological developments are certainly something that makes the community happy, because with technology, people can save time in doing things that are often done in daily activities. Now, Zakat institutions are also trying to develop technology in their operations, including in the collection of zakat funds. This is based on the increasing demand from the community who want to fulfill their obligations as Muslims, but with greater time efficiency. In this era, almost all community activities use technology, because it is considered safer and more convenient. However, the problem faced is that many people still do not understand the application of technology in ZIS institutions, even though the Indonesian people are enthusiastic about distributing ZIS, especially since the collection is technology-based. Therefore, technology currently plays a very important role in the collection of ZIS funds in Indonesia.